Effects of arsenic on physiology, anatomy and transcriptomes on aquatic plants - Atabaki, Narges (2021)
The presence of arsenic in groundwater has affected the water supply, especially in rural areas. Inorganic arsenic can be transferred to the food chain through water contamination and causes acute biotoxicity. Selecting appropriate aquatic plants tolerant to arsenic contamination are the key factors in promoting the practical application of phytoremediation in a polluted environment. Water hyacinth (Eichhornia crassipes) and water mimosa (Neptunia oleracea) have been widely identified as two feasible phytoremediators. In the current study, the phytoremediation potential of water hyacinth and water mimosa exposed to different concentrations of sodium heptahydrate arsenate (5, 10, 30, 50, 60, 70, 80, 90, and 100 mg/L) was tested for two weeks. Several plant physiological and growth responses as well as arsenic accumulation and removal efficacy were analyzed. It was found that there were significant differences in the level of 5% for all the traits between the arsenic treatments for both types of plants. In water hyacinth and water mimosa, there were decreasing trends of the ratio of biomass (DRB), the ratio of dry weight (DRD), photosynthetic activities, stomatal conductance, intercellular CO2, transpiration rate, air pressure deficit and chlorophyll content after 14 days of exposure to the arsenic. In the experiment, water hyacinth had shown the highest arsenic absorption as compared to the water mimosa, which was recorded at 70 mg/L. Water mimosa showed severe necrotic symptoms at the highest concentrated condition (100 mg/L) after 14 days of treatment but was still able to accumulate 16.36 mg/Kg-1 arsenic in its roots (0.8 mg total arsenic). To have a further understanding at the molecular level, transcriptomic analysis was performed on the arsenic-treated water hyacinth using the RNA-Sequencing technique. Differential gene expressions had uncovered transcripts encoding various genes associated with the arsenic uptake, the effect on the structural constituent of the ribosome in the plant as well as heat shock tolerance mechanisms. Accordingly, the expression of intracellular ribonucleoprotein complex, suggesting a potential means for arsenic impact on RNA-binding proteins and RNA to denote intracellular compartments involved in the processing of RNA transcripts. All in all, water hyacinth and water mimosa have the potential to be a phytoremediator plant. Their response to the heavy metal contamination, coupled with high biomass yields, makes them a considerable option for contaminated site phytoremediation.